INCREASING STUDENTS' READING COMPREHENSION OF RECOUNT TEXT THROUGH PICTURES IN CAROUSEL BRAINSTORMING STRATEGY FOR 8TH GRADE AT MTS TAQWIYATUL WATHON ACADEMIC YEAR 2022/2023 - Endang Nadya Lestari; Moh. Wahyu Widiyanto; Fitri Yulianti (Bajang Institute, 2023)
The purpose of the research was to compare students' levels the extent of comprehension before and after being introduced to Carousel brainstorming strategy for reading recount texts through pictures. The research methodology is a quantitative pre-experimental research design. The sample was 33 students of Eight grade A at MTs Taqwiyatul Wathon. The instrument for research consisted of a pre-test and a post-test. The researcher employed Indonesian KKM (Minimum completeness criteria) at MTs Taqwiyatul Wathon with the KKM score of 70 as the criterion. pre test results indicate were 6,06% met the KKM criteria, and the post test results were 78,8% accomplishing the KKM standards. The researcher also employed the N-Gain method to ascertain whether or not the addition of recount text through pictures in Carousel brainstorming strategy. In this case, the The N-Gain Formula resulted in a mean value of 58.3155. Students' reading comprehension dramatically increase after being introduced to recount text through pictures in Carousel brainstorming strategy